Environmental Risk Regulation in the Environmental Protection Law of the Republic of Slovenia - Ticar, Bojan (Communications - Scientific Letters of the University of Zilina, 2011)
The purpose of this paper is to present an overview of the regulation of environmental protection in force in administrative law in the Republic of Slovenia. The author analyses basic environmental protection principles which are contained in the EU regulation. These principles are: (1) the precautionary principle (le principe de précaution, der Grundsatz der Vorsorge), (2) the principle of preventive action (le principe d'action préventive, der Grundsatz der Vorbeugung), (3) the principle of correction at source (le principe de correction à la source, der Grundsatz, Umweltbeeinträchtigungen mit Vorrang an ihrem Ursprung zu bekämpfen), and (4) the polluter pays principle (le principe de pollueurpayeur, das Verursacherprinzip).In order to accede to the EU, the Republic of Slovenia in Article 3a of the Constitution of the Republic of Slovenia allowed the supremacy of the primary legislation of the EU over Slovenian national regulations. The above-mentioned principles of the EC Treaty are transposed into the legal system of the Republic of Slovenia by means of its environmental legislation and implementing regulations. In this paper the author analyses the public law regulation contained primarily in the Environmental Protection Act (Official Gazette RS, Nos. 39/2006, 20/2006, and 70/2008). In addition to the general regulation implemented already by the Environmental Protection Act of 2006, the last amendment to the Environmental Protection Act transposed into the Slovenian legal order the provisions of Directive 2004/35/CE of the European Parliament and of the Council of 21 April 2004 on environmental liability with regard to the prevention and remedying of environmental damage.The paper focuses on the administrative legal regulation of the prevention and reduction of burdens on the environment, the conservation and improvement of the quality of the environment, the remedying of the consequences of burdens on the environment, as well as the improvement of the disrupted natural equilibrium and the recovery of its regenerative capacity. The paper furthermore analyses the application of the Environmental Protection Act as a general substantive law, as well as the special application of the procedures provided for in the Environmental Protection Act against subsidiary regulation of general administrative procedures in cases in which public and private interests are in collision or in potential collision.
Keywords: administrative law; environmental protection; the precautionary principle; the principle of preventive action; the principle of correction at source; the polluter pays principle